HUBUNGAN PERTUKARAN PEMIMPIN-ANGGOTA DENGAN KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL YANG DIMEDIASI OLEH KEADILAN ORGANISASIONAL - Vibriwati Vibriwati (KINERJA, 2005)
This research was developed and conducted to test a model for examining the influence ofleader-member exchange (LMX) on job satisfaction, organizational commitment and organizational justice that was used as mediating variables. The subjects of the research was one hundred and seventy nine employees in four oil companies. The application of structural equation modelling on the predicted model showed that leader-member exchange (LMX) affected job satisfaction and organizational commitment through its effects on organizational justice.Keywords: LMX, organizational justice, job satisfaction, organizational commitment.